Osteogenic differentiation of 3D-printed porous tantalum with nano-topographic modification for repairing craniofacial bone defects - Zhang, Chuxi; Zhou, Zhongwei; Liu, Nian; Chen, Jiangping; Wu, Jinyang; Zhang, Yong; Lin, Kaili; Zhang, Shilei (Frontiers in Bioengineering and Biotechnology, 2023)
Congenital or acquired bone defects in the oral and cranio-maxillofacial (OCMF) regions can seriously affect the normal function and facial appearance of patients and cause great harm to their physical and mental health. To achieve satisfying bone defect repair results, the prosthesis requires good osteogenic ability, appropriate porosity, and precise three-dimensional shape. Tantalum (Ta) with better mechanical properties, osteogenic ability, and microstructure compared to Ti6Al4V has become a potential alternative material for bone repair. The bones in the OCMF region have unique shapes, and three-dimensional (3D) printing technology is currently the method of choice for manufacturing personalized prosthesis with complex shapes and structures. Moreover, the surface characteristics of materials, such as surface morphology, also affect the biological behavior of cells, among which nano-topographic surface modification enables to provide materials with unique surface properties such as wettability and large surface area, enhancing the adhesion of osteoblasts and thereby enhancing their osteogenic ability. In this study, porous tantalum scaffolds were fabricated by 3D printing, and nano-topographic was constructed by alkali-thermal-hydrothermal treatment to verify their osteogenic ability through a series of in vivo and in vitro experiments. The research shows that porous tantalum modified by nano-topographic surface do promote the proliferation and osteogenic differentiation of BMSCs and accelerate the formation of new bone in the angle of the mandible bone defect of rabbits. It can be seen that 3D-printed nano-topographic surface modified porous tantalum has broad application prospects in the repair of OCMF bone defects.